2013
DOI: 10.1523/jneurosci.2954-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of p62/Sequestosome 1 Causes Hyperphagia Due to Leptin Resistance in the Brain

Abstract: The cytoplasmic regulatory protein p62 (Sequestosome 1/A170) is known to modulate various receptor-mediated intracellular signaling pathways. p62 deficiency was shown to result in mature-onset obesity in mice, but the mechanisms underlying this abnormality remained unclear. Here we report that hyperphagia due to central leptin resistance is the cause of obesity in p62 Ϫ/Ϫ mice. We found that these mice show hyperphagia. Restriction of food to the amount eaten by wild-type mice prevented excess body weight gain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 58 publications
1
46
0
Order By: Relevance
“…In this study, we developed genetically modified mice with decreased 26S proteasome activity, which accumulate aggregate structures positive for both ubiquitin and p62 in their cells, and found that proteasome-dysfunction activates selective autophagy and the Keap1-Nrf2 pathway, both of which serve as cellular defense mechanisms. , and the Nrf2-knock-out mice used in this study were described previously (33)(34)(35). Mice were housed in specific pathogen-free facilities, and the Ethics Review Committee for Animal Experimentation of the Tokyo Metropolitan Institute of Medical Science approved the experimental protocols.…”
Section: Rpt2mentioning
confidence: 99%
“…In this study, we developed genetically modified mice with decreased 26S proteasome activity, which accumulate aggregate structures positive for both ubiquitin and p62 in their cells, and found that proteasome-dysfunction activates selective autophagy and the Keap1-Nrf2 pathway, both of which serve as cellular defense mechanisms. , and the Nrf2-knock-out mice used in this study were described previously (33)(34)(35). Mice were housed in specific pathogen-free facilities, and the Ethics Review Committee for Animal Experimentation of the Tokyo Metropolitan Institute of Medical Science approved the experimental protocols.…”
Section: Rpt2mentioning
confidence: 99%
“…Further studies will hence be needed to determine the molecules that may compensate for p62 in p62 f/f :RIP-Cre mice. Harada et al reported that brain-specific p62 disruption by nestin-Cre results in significant body weight gain compared with control mice at 20 weeks of age [20]. Importantly, pair feeding completely abolished the obese phenotype of brain-specific p62 KO mice, indicating that p62 in the brain inhibits appetite and thus controls body weight homeostasis [20].…”
Section: Discussionmentioning
confidence: 99%
“…Harada et al reported that brain-specific p62 disruption by nestin-Cre results in significant body weight gain compared with control mice at 20 weeks of age [20]. Importantly, pair feeding completely abolished the obese phenotype of brain-specific p62 KO mice, indicating that p62 in the brain inhibits appetite and thus controls body weight homeostasis [20]. It has been demonstrated that RIP-Cre is expressed in a subset of neurons in the hypothalamus, and that deletion of Stat3 results in progressive obesity [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations